Work motivation factors among call centre employees in India - jakka, sai sashank (2011)
Abstract Background: Throughout the history of humankind, the driving influence of motivation in achieving set goals and targets is well established. It is interesting how this primal urge to achieve a target continues to inspire achievement in many modern occupations. The call-centre culture of urban India provides an ideal case-study to investigate just that as employees continue to produce positive results despite the existence of several significant deterrents. This study seeks to explore role of motivation in call-centre employees in India in context of Herzberg’s and Maslow’s theories of motivation. Methodology: A qualitative approach was followed in this project. A structured self-completion questionnaire was prepared by the author and sent to potential participants. The questionnaire was devised based on the five most important factors- working conditions; financial rewards and fringe benefits; team managers; organizational climate and culture; personal attributes- that have a direct impact on the motivation of the members of the sample. The self-completion questionnaire was sent to 55 call-centre employees out of which there were 34 respondents. The results so obtained were interpreted using appropriate graphs and charts. Results: The survey revealed that, call-centre employees in India considered Job Security (Total rank score-191), Training (Total rank score-173) and Job Promotion (Total rank score-138) as their top three most important motivational factors. Pay Rate (Total rank score-137), which is generally thought of as being the most important motivating factor, was shown to be considered only as the fourth most important motivating factor. Other factors, namely Work Appreciation (Total rank score-124), Fringe Benefits (Total rank score-94) and Status (Total rank score-67) were revealed to be the fifth, sixth and seventh most important motivational factors respectively. These results along with comparative analyses of different motivating factors have been presented in the form of graphs where appropriate.